2018
DOI: 10.1038/s41598-018-34733-9
|View full text |Cite|
|
Sign up to set email alerts
|

Earth tectonics as seen by GOCE - Enhanced satellite gravity gradient imaging

Abstract: Curvature components derived from satellite gravity gradients provide new global views of Earth’s structure. The satellite gravity gradients are based on the GOCE satellite mission and we illustrate by curvature images how the Earth is seen differently compared to seismic imaging. Tectonic domains with similar seismic characteristic can exhibit distinct differences in satellite gravity gradients maps, which points to differences in the lithospheric build-up. This is particularly apparent for the cratonic regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 53 publications
0
38
0
Order By: Relevance
“…Satellite data are particularly well suited to overcome the remoteness of the Antarctic continent, as they have an almost global uniform coverage (Ebbing et al, ). In contrast to surface and airborne surveys, satellite measurements also contain consistent long‐wavelength (>150 km) information, which is mainly influenced by deep subsurface structures (Sebera et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Satellite data are particularly well suited to overcome the remoteness of the Antarctic continent, as they have an almost global uniform coverage (Ebbing et al, ). In contrast to surface and airborne surveys, satellite measurements also contain consistent long‐wavelength (>150 km) information, which is mainly influenced by deep subsurface structures (Sebera et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, satellite gravity gradient data can be used in combination with seismological models to derive lithospheric models. The potential of satellite-based gravity gradients to establish regional models, which can be used as a background for local interpretations, has been demonstrated (Bouman et al, 2015;Holzrichter & Ebbing, 2016) and is especially useful for large, inaccessible areas such as the Antarctic continent (Ebbing et al, 2018). Since the gravity gradients possess different sensitivities for different depth ranges (Bouman et al, 2016), they are particularly suited to investigate the mass distribution within the lithosphere.…”
Section: Introductionmentioning
confidence: 99%
“…Satellite‐derived measurements of the Earth's gravity field can be used to observe density variations within the planet (Barzaghi et al, ; Ebbing et al, ). Applications of these data for evaluation of the lithosphere have concentrated on the mantle (e.g., density and stress state and determination of the Mohorovic discontinuity; Bouman et al, ; Panet et al, ; Uieda & Barbosa, ; Van der Meijde et al, ), with much less emphasis on the crustal structures (Bouman et al, ; Braitenberg, ; Ebbing et al, ; Van der Meijde et al, ). Crustal studies have shown distinctive characteristics in the framework of the African and South American continents (Braitenberg, ) with data from the Gravity Field and Steady‐State Ocean Circulation mission.…”
Section: Introductionmentioning
confidence: 99%